Magnetic resonance cholangiopancreatography enhanced by virtual reality as a novel tool to improve the understanding of biliary anatomy and the teaching of surgical trainees - Staubli, Sebastian M.; Maloca, Peter; Kuemmerli, Christoph; Kunz, Julia; Dirnberger, Amanda S.; Allemann, Andreas; Gehweiler, Julian; Soysal, Savas; Droeser, Raoul; Däster, Silvio; Hess, Gabriel; Raptis, Dimitri; et al. (Frontiers in Surgery, 2022)
Objective: The novel picture archiving and communication system (PACS), compatible with virtual reality (VR) software, displays cross-sectional images in VR. VR magnetic resonance cholangiopancreatography (MRCP) was tested to improve the anatomical understanding and intraoperative performance of minimally invasive cholecystectomy (CHE) in surgical trainees. Design: We used an immersive VR environment to display volumetric MRCP data (Specto VRTM). First, we evaluated the tolerability and comprehensibility of anatomy with a validated simulator sickness questionnaire (SSQ) and examined anatomical landmarks. Second, we compared conventional MRCP and VR MRCP by matching three-dimensional (3D) printed models and identifying and measuring common bile duct stones (CBDS) using VR MRCP. Third, surgical trainees prepared for CHE with either conventional MRCP or VR MRCP, and we measured perioperative parameters and surgical performance (validated GOALS score). Setting: The study was conducted out at Clarunis, University Center for Gastrointestinal and Liver Disease, Basel, Switzerland. Participants: For the first and second study step, doctors from all specialties and years of experience could participate. In the third study step, exclusively surgical trainees were included. Of 74 participating clinicians, 34, 27, and 13 contributed data to the first, second, and third study phases, respectively. Results: All participants determined the relevant biliary structures with VR MRCP. The median SSQ score was 0.75 (IQR: 0, 3.5), indicating good tolerability. VR MRCP provided a faster and more accurate understanding of the anatomy compared to conventional MRCP with printed MRCP models: We obtained a median of 90 s (IQR: 55, 150) and 72.7 % correct answers with VR MRCP versus 150 s (IQR: 100, 208) and 49.6 % correct answers with conventional MRCP, respectively (p < 0.001). CBDS was correctly identified in 90.5 % of VR MRCP cases. The median GOALS score was higher after preparation with VR MRCP than with conventional MRCP for CHE: 16 (IQR: 13, 22) and 11 (IQR: 11, 18), respectively (p = 0.27). Conclusions: VR MRCP allows for a faster, more accurate understanding of displayed anatomy than conventional MRCP and potentially leads to improved surgical performance in CHE in surgical trainees.